(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Caesalpinia pulcherrima is a medicinal plant belonging to the family Caesalpiniaceae. The main aim of the present study was to investigate the Anti Arthritic activity of the ethanolic extract of Caesalpinia pulcherrima (ECP) at the dose of 200 mg/kg and 400 mg/kg on Type II Collagen induced Arthritis in experimental rats. In collagen induced arthritic rats, there was significant enhance in rat paw volume and reduce in body weight, whereas ECP and Aspirin treated groups showed significant decrease in paw volume and normal gain in body weight. The altered hematological parameters (Hb, RBC, WBC, ESR and CRP) in the arthritic rats were significantly recover to normal by administration of ECP. Further the radiological studies revealed the anti arthritic activity of ECP by indicating less abnormality in extract treated groups when compared to the arthritic control group. Findings from the present investigations suggest that the ethonolic extract of Caesalpinia pulcherrima exhibits significant anti arthritic activity.